2018
DOI: 10.5455/jice.20170926111217
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Content and In vitro Diphenylpicrylhydrazyl Free Radical Scavenging Activity of Selected Medicinal Plants

Abstract: Background/Aim: The medicinal plants and their derivatives have long been recognized as important sources of antioxidants in the prevention and treatment of various diseases. This study investigated phytochemicals, antioxidant content, and in vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activities of methanolic and aqueous leaves extracts of Anogeissus leiocarpus, Ipomoea asarifolia, Bauhinia rufescens, Guiera. Senegalensis, and Moringa oleifera. Materials and Methods:The extracts were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…The phytochemical investigation revealed the presence of alkaloids, flavonoids, and tannins in the same plants, but the phenolic and proanthocyanidin contents of methanolic extracts were significantly higher as compared with aqueous extracts. The authors concluded that DPPH-free radical scavenging activity of methanolic extracts of A. leiocarpus and M. oleifera was similar to vitamin C and was better expressed as compared with B. refescens, I. asarifolia, G. senegalensis ( 145 ). A similar antioxidative effect and DPPH-free radical scavenging activity was also reported for methanolic extract of Desmodium ramosissimum, which could be another rich source of natural antioxidants, justifying its pharmacological use in traditional medicine ( 178 ).…”
Section: Plant and Herbal Additives As A Safe Approach To Combat Harm...mentioning
confidence: 99%
“…The phytochemical investigation revealed the presence of alkaloids, flavonoids, and tannins in the same plants, but the phenolic and proanthocyanidin contents of methanolic extracts were significantly higher as compared with aqueous extracts. The authors concluded that DPPH-free radical scavenging activity of methanolic extracts of A. leiocarpus and M. oleifera was similar to vitamin C and was better expressed as compared with B. refescens, I. asarifolia, G. senegalensis ( 145 ). A similar antioxidative effect and DPPH-free radical scavenging activity was also reported for methanolic extract of Desmodium ramosissimum, which could be another rich source of natural antioxidants, justifying its pharmacological use in traditional medicine ( 178 ).…”
Section: Plant and Herbal Additives As A Safe Approach To Combat Harm...mentioning
confidence: 99%
“…Il possédait une activité antioxydante considérable contre le radical DPPH (Abubakr et al, 2013). Muhammad et al (2018) ont réalisé une étude sur les activités de piégeage des radicaux libres 2,2-diphényle-1picrylhydrazyle (DPPH) des extraits méthanoliques et aqueux de feuilles G. Senegalensis. Les deux extraits présentaient une activité antioxydante (Muhammad et al, 2018).…”
Section: Activité Antioxydanteunclassified